Theoretical Studies of the Electronic and Thermoelectric Properties of PrIn₃ and NdIn₃ in Cubic Phase - Naz, Aiddah; Ullah, Qasim; Khan, Banaras (London Journal of Physics, 2024)
The electronic and thermoelectric properties of AB3 (A =Pr, Nd and B=In) materials (crystallizing in the cubic structure) having space group Pm-3m (221) are studied using B3PW91 hybrid functional through the Full-Potential Linear Augmented Plane Wave (FP-LAPW) approach within the framework of Density Functional Theory (DFT). The calculated lattice parameters for PrIn3 and NdIn3 are 4.5668 Å and 4.5539 Å respectively. Electron-electron correlation effect is due to the 4f orbitals present in these materials and therefore, with the use of B3PW91 hybrid functional, band structure and density of states are calculated. When analyzing electron charge density, these materials showed a stronger ionic character. Band structure and density of state analysis confirms the metallic nature of the materials. Using the semi-empirical Boltzmann approach implemented in the BoltzTraP code, the thermoelectric parameters, such as Seebeck coefficient, figure of merit, electrical conductivity per relaxation time, and electronic thermal conductivity per relaxation time as a function of chemical potential, were computed at 500 K temperature gradient. PrIn3 showed highest Seebeck coefficient value, 50.68 μV/K among these compounds. The peak value of electrical conductivity per relaxation time and electronic thermal conductivity per relaxation time among these compounds is calculated for NdIn3 is 2.43 x 1020 1/Ωms and 22.50×1014 W/mKs.